Substâncias húmicas: sistema de fracionamento sequencial por ultrafiltração com base no tamanho molecular - Rocha, Julio Cesar [UNESP] (2000)
A sequential system for fractionation by ultrafiltration (SSFU) equipped with advanced membranes filters (molecular size cut-off: 5, 10, 30, 50 and 100 kDalton) of the polyethersulfone type was developed for analytical fractionation of humic substances (HS) extracted from aquatic systems or soils. The device consists of five membrane filters (Sartocon® Micro) operated by a multi-channel peristaltic pump, enabling an easy handling, working in a closed system and with simple collection of the six obtained fractions (F1>100; F2: 100-50; F3: 50-30; F4:30-10; F5: 10-5 and F6 <5 kDalton). Then, the HS sample (250 mL solution 1.0 mg/mL, pH 5.0 to 6.0) to be fractionated is pumped by pump through the series of membrane filters with a tangential flow of 85 mL/min, initial pressure 0.2 to 0.3 bar and permeation flux through the membranes of 0.8 to 1.4 mL/min. The overall time for fractionation and cleaning of the device is about 10 h and 25 mL of each fraction is obtained.